Unemployment and politics - "Harris, Jose" (Oxford, 1972)
This study examines the recurring problem of unemployment in the period when it first began to assume its modern shape, between the economic recession of the 1880s and the outbreak ofthe First World War. The author discusses the many different ways in which the social phenomena of unemployment and poverty were perceived and analysed, and how these theoretical developments moulded the rival social policies for relieving unemployment put forward by Beveridge, the Webbs, Balfour, Lloyd George, and others.
Keywords: Economics